The effects of Awe in religious tourism: Can augmented reality play an important role? - Afonso, Maria Rita Nogueira da Silva (2022)
Religious Tourism has been one of the most important forms of Heritage Cultural Tourism, attracting millions of visitors each year to sacred places, where they usually experience the emotion of AWE. Furthermore, Augmented Reality (AR) was identified as a prominent technology that allows the touristic experience to be enhanced. That said, this dissertation explores the impact of AWE on religious tourists’ experiences and the effect of AR on it. An online survey was developed and presented to religious tourists that were exposed to AR and to religious tourists that weren’t. A total of 158 responses were collected and analyzed. It was concluded that experiencing awe in religious tourism might influence the perception of authenticity from tourists (both object-based authenticity, and existential authenticity). Furthermore, results show that the awe experience is also positively related to the experience of positive emotions by the religious tourist and negatively related to negative emotions. Moreover, the perception of existential authenticity and positive emotions are positively related to the intention of revisiting the said religious tourism destination. The perception of object-based authenticity and existential authenticity also present a significant positive relation to the intention to recommend the touristic destination to friends and family. It was also concluded that a tourist that feels negative emotions will not have the intention to recommend the destination. Moreover, it was concluded that the AR experience, not having a significant effect on the touristic experience, can be used as a complement to typical touristic experiences, especially to attract younger generations.